2020
DOI: 10.1038/s41419-020-2696-5
|View full text |Cite|
|
Sign up to set email alerts
|

Advances and potential pitfalls of oncolytic viruses expressing immunomodulatory transgene therapy for malignant gliomas

Abstract: Glioblastoma (GBM) is an immunosuppressive, lethal brain tumor. Despite advances in molecular understanding and therapies, the clinical benefits have remained limited, and the life expectancy of patients with GBM has only been extended to~15 months. Currently, genetically modified oncolytic viruses (OV) that express immunomodulatory transgenes constitute a research hot spot in the field of glioma treatment. An oncolytic virus is designed to selectively target, infect, and replicate in tumor cells while sparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 131 publications
(155 reference statements)
0
46
0
Order By: Relevance
“…OVs drive tumor cell death, resulting in the release of inflammatory signals (cell stress danger-associated molecular patterns or DAMPS) and the liberation of tumor-associated antigens to promote anti-tumor immunity. Most recently, clinical trials in patients with brain tumors have shown promising results using OVs ( 144 ), such as PVSRIPO (a modified poliovirus OV) in patients with glioblastoma, where some patients have shown complete and durable remissions ( 145 ). Future investigations into combinatorial approaches may further enhance the outcomes of OVs in tumors and help delineate which patients with brain tumors may require additional resections vs. orthogonal treatment combinations.…”
Section: Simulating a “Small” Immune Microenvironmentmentioning
confidence: 99%
“…OVs drive tumor cell death, resulting in the release of inflammatory signals (cell stress danger-associated molecular patterns or DAMPS) and the liberation of tumor-associated antigens to promote anti-tumor immunity. Most recently, clinical trials in patients with brain tumors have shown promising results using OVs ( 144 ), such as PVSRIPO (a modified poliovirus OV) in patients with glioblastoma, where some patients have shown complete and durable remissions ( 145 ). Future investigations into combinatorial approaches may further enhance the outcomes of OVs in tumors and help delineate which patients with brain tumors may require additional resections vs. orthogonal treatment combinations.…”
Section: Simulating a “Small” Immune Microenvironmentmentioning
confidence: 99%
“…Oncolytic virotherapy may also circumvent mesenchymal transition in GBM by promoting the polarization state of TAMs as pro-inflammatory and antitumoral M1 phenotype. As it was discussed in the recent review by Zhang and Liu, genetically modified oncolytic viruses expressing immunomodulatory transgenes have been considered as a promising therapeutic tool for glioma treatment [ 182 ]. Combined treatment of oncolytic herpes simplex virus expressing IL-12 with two checkpoint inhibitors (anti-CTLA-4 and anti-PD-1) resulted in the regression of GBM tumor in a preclinical mouse model and, interestingly, this treatment was found to be associated with influx of macrophages of M1-like polarization state [ 132 ].…”
Section: The Transcriptome Of Mesenchymal Glioblastomamentioning
confidence: 99%
“…Gliomas can be divided into various subtypes according to their histological characteristics [4]. Although great progress has been made in the diagnosis and treatment of glioma in the past decades, the prognosis is still poor [5,6]. The 5-year survival rate of low-grade glioma patients is about 30 ~ 70%, while the median survival time of GBM patients is 9 ~ 12 months [7,8].…”
Section: Introductionmentioning
confidence: 99%